Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1037/0022-3514.61.2.212
|View full text |Cite
|
Sign up to set email alerts
|

Group members' reactions to opinion deviates and conformists at varying degrees of proximity to decision deadline and of environmental noise.

Abstract: Four experiments examined freely interacting groups to investigate the determinants of group members' reactions to opinion deviates and conformists. In the 1st experiment, the deviate was rejected more when he or she articulated the dissenting opinion in close proximity to the group-decision deadline versus at an earlier point in the group discussion. In the 2nd, 3rd, and 4th experiment, the deviate was rejected more when the group discussion was carried out in a noisy versus a quiet environment. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
255
1
5

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 252 publications
(271 citation statements)
references
References 21 publications
(25 reference statements)
9
255
1
5
Order By: Relevance
“…While the aforementioned studies provided direct evidence for the link between social attitudes and NFC, other studies provided additional, indirect evidence for this relation by showing that high need for closure individuals are more likely to prefer autocratic leadership (Pierro, Mannetti, De Grada, Livi, & Kruglanski, 2003) and to derogate deviants (Kruglanski & Webster, 1991). Moreover, other research also revealed significant relationships between NFC and prejudice, showing that high (vs. low) NFC scorers tend to favour ingroups and derogate outgroups (Golec, Federico, Cislak, & Dial, 2005;Kruglanski, Pierro, Mannetti, & De Grada, 2006).…”
Section: The Relationship Between Social Attitudes and Cognitive Funcmentioning
confidence: 99%
“…While the aforementioned studies provided direct evidence for the link between social attitudes and NFC, other studies provided additional, indirect evidence for this relation by showing that high need for closure individuals are more likely to prefer autocratic leadership (Pierro, Mannetti, De Grada, Livi, & Kruglanski, 2003) and to derogate deviants (Kruglanski & Webster, 1991). Moreover, other research also revealed significant relationships between NFC and prejudice, showing that high (vs. low) NFC scorers tend to favour ingroups and derogate outgroups (Golec, Federico, Cislak, & Dial, 2005;Kruglanski, Pierro, Mannetti, & De Grada, 2006).…”
Section: The Relationship Between Social Attitudes and Cognitive Funcmentioning
confidence: 99%
“…Second, treating political conservatism solely as an individualdifference variable neglects growing evidence that situational factors influence the experience and expression of conservatism (e.g., Crowe & Higgins, 1997;Greenberg et al, 1990;Jost, Kruglanski, & Simon, 1999;Kruglanski & Webster, 1991;Sales & Friend, 1973;Sulloway, 1996Sulloway, , 2001. If classic personality theories are correct in positing that character rigidity and motivational threat are related to the holding of conservative attitudes, then system instability and other threatening circumstances should also increase conservative tendencies in the population as a whole (e.g., Fromm, 1941;McCann, 1997;Reich, 1946Reich, /1970Sales, 1972Sales, , 1973Sanford, 1966).…”
mentioning
confidence: 99%
“…Among the effects of the two tendencies, one is of particular interest -the firm belief of people with high need for closure in the validity of their judgments (Kruglanski & Webster, 1991;Kruglanski, Webster, & Klem, 1993;Webster, 1993). This effect is paradoxical because it is contrary to the common belief that what is needed in order to formulate complete and certain knowledge is more extensive processing of the available information rather than filtering it and limiting the processing (Kruglanski & Webster, 1996).…”
Section: The Dual Consequences Of the Need For Closure And The Need Tmentioning
confidence: 53%
“…One last thing worth noting is that even though knowledge acquisition is conceptualized in a formal manner, the theory does not state that the individual must know the rules of formal logic, that the process is carried out exclusively consciously, or that knowledge always takes the form of an abstract, consciously accessible rule (Erb et al, 2003). On the contrary, the process usually takes place unconsciously and people do not need to be aware of the factors that influence them (e.g., Kruglanski & Webster, 1991). The theory also allows for a variety of errors, for instance better or worse coping with a problem depending on the level of its abstraction (Evans, 1989), unjustified assignment of meaning to objectively irrelevant premises and vice versa (Crocker, Hannah, & Weber, 1983), and -lastly -reasoning errors (e.g., Wason, 1966).…”
Section: The Formulation Of a Scientific Theory As Analogous To Commomentioning
confidence: 99%